Identification of vibrio species isolated from marine fish using polymerase chain reaction - Bahari, Muhamad Faiz; Mohd Yusoff, Sabri (2011)
Vibrio species are found in marine and estuarine environments. Vibriosis can cause more than 50% mortality in fish culture facilities once an outbreak is in progress. The objectives of this study were to subculture and identify Vibrio spp. that were isolated previously from marine fish; to develop a technique for simultaneous identification of several Vibrio spp. (V. alginolyticus, V. parahaemolyticus, V. fluvialis and V. vulnificus) using polymerase chain reaction (PCR); and to compare the rapid identification kit and PCRtechniques commonly used for the identification of the Vibrio spp. In this study, 20 isolates from four Vibrio species, which consisted of five eachof V. alginolyticus, V. parahaemolyticus, V. fluvialis and V. vulnificus isolates were provided by National Fish Health Research Centre (NaFisH). The species of Vibrio were identified using an identification kit, API 20E system. These organisms were isolated from various marine fish such as Asian Seabass (Latescalcarifer), Grouper (Epinepheluscoioides), Silver Pomfret (Pampusargenteus) and Red Snapper (Lutjanuscampechanus). The isolates were previously stored at -80°C and subcultured onto TSA+. The pure cultures were then transferred to TSB+. These isolates were subjected to DNA extraction. Once the DNA is ready, PCR was used to optimise the products with the designated primers. All the PCR products were electrophoresed through 1% agarose gel for 1 h. The designated primers in this study were found suitable for the detection of V. alginolyticus,V. parahaemolyticus,V. fluvialis and V. vulnificus.Using the API 20E system, 15% (3/20) isolatesof Vibrio spp. were negative, indicating the the PCR technique is still required to confirm the result obtained by the use of the API 20E system.